THE RELATIONSHIP OF LIPID PROFILE INDICATORS WITH INFLAMMATORY MEDIATORS AND FIBRINOGEN IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (Modern American Journal of Social Sciences and Humanities, 2025)
Systemic lupus erythematosus (SLE) is an inflammatory rheumatic disease of autoimmune origin, which is more common in women. This disease involves a generalized inflammatory process that affects numerous internal organs and tissues. Patients with SLE also experience accelerated development of atherosclerosis and cardiovascular complications. The relationship between lipid metabolism disorders and inflammation plays a key role in this situation. This article analyzes the relationship between lipid metabolism disorders and inflammation in patients with systemic lupus erythematosus (SLE). Specifically, it examines the correlation of lipid profile parameters—total cholesterol, triglycerides, and high- and low-density lipoproteins—with acute-phase reactants such as C-reactive protein, ceruloplasmin, and fibrinogen. Based on an analysis of existing clinical and biochemical studies, the significance of these parameters and their potential use as prognostic markers are discussed.